The Influence of Translation Technique on Translation Ideology in the Novel - Supatmiwati, Diah; Anggara, Gde Wetan Pragena; Syahid, Agus (LPPM Universitas Bumigora Mataram, 2024)
Translation is extremely crucial when communicating information, culture, messages, and so on between two or more people who speak different languages. The problem arises when it comes to translate a fantasy stories or games because the translation technique and ideology are heavily relied on the culture. This research aims to find out the influence of translation technique on ideology in translating the novel â€œOverlordâ€. This method of this research is qualitative, and the data collected is used to determine the analytical unit, which is the fantasy novel